2004
DOI: 10.1111/j.1468-2982.2004.00681.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Headache in Swedish Schoolchildren, with a Focus on Tension-Type Headache

Abstract: To estimate the prevalence of tension-type headache, migraine and other headaches, 1850 schoolchildren, age 7-15 years, from the city of Uppsala, were invited to complete a questionnaire. The response rate was 74.1%. To validate the information from the questionnaires, 131 children and their parents were interviewed. Using the criteria of the International Headache Society, the 1-year prevalence of tension-type headache and migraine was 9.8 and 11.0%, respectively. However, these prevalence rates increased con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

31
209
8
11

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(259 citation statements)
references
References 35 publications
31
209
8
11
Order By: Relevance
“…Population-based studies reported that the prevalence of migraine in childhood and adolescence ranges from 3% to 14% [1][2][3][4][5][6]. From the time of Wolff's early portrait of the childhood personality characteristics of migraine patients, the research began to explore the association of headache first with broad personality traits and then with distinct psychiatric symptoms [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Population-based studies reported that the prevalence of migraine in childhood and adolescence ranges from 3% to 14% [1][2][3][4][5][6]. From the time of Wolff's early portrait of the childhood personality characteristics of migraine patients, the research began to explore the association of headache first with broad personality traits and then with distinct psychiatric symptoms [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported annual prevalence rates in children of between 3% and 11% for migraine, [4][5][6] and between 10% and 24% for tensiontype headache. 4,7 The prevalence of 'self-reported' headache is higher. Between 6.5% and 30% of children and adolescents report headaches weekly or more frequently.…”
Section: Introductionmentioning
confidence: 99%
“…Majority of the information available is limited to hospital-based studies or school surveys which may not reflect the true dimensions of the disorders prevalent in a community. Among the most common representative primary headaches in children, some studies point migraines and others as tension type headache [8][9][10][11] .…”
Section: Epidemiologymentioning
confidence: 99%